System-level design of bacterial cell cycle control - McAdams, Harley H. (2009)
Understanding of the cell cycle control logic in Caulobacter has progressed to the point where we now have an integrated view of the operation of an entire bacterial cell cycle system functioning as a state machine. Oscillating levels of a few temporally-controlled master regulator proteins in a cyclical circuit drive cell cycle progression. To a striking degree, the cell cycle regulation is a whole cell phenomenon. Phospho-signaling proteins and proteases dynamically deployed to specific locations on the cell wall are vital. An essential phospho-signaling system integral to the cell cycle circuitry is central to accomplishing asymmetric cell division.